Controllable deuteration of halogenated compounds by photocatalytic D2O splitting - Cuibo Liu (Nature Portfolio, 2018)
Developing convenient deuterium labeling procedures is important in organic synthesis and the pharmaceutical industry. Here, the authors report a mild photocatalytic strategy for controllable deuteration of halides using D2O as the reagent and porous CdSe nanosheets as the catalyst.